Waves of visibility: probing the depth of inter-ocular suppression with transient and sustained targets - Kaunitz, Lisandro N.; Fracasso, Alessio; Skujevskis, Māris; Melcher, David (Frontiers in Psychology, 2014)
In order to study non-conscious visual processing, researchers render otherwise consciously perceived images into invisible stimuli. Through the years, several psychophysical techniques have been developed for this purpose. Yet the comparison of experimental results across techniques remains a difficult task as the depth of suppression depends on the interactions between the type of stimuli and the suppression methods employed. This poses a limit to the inferences that researchers make about the extent of non-conscious processes. We investigated the mechanisms underlying inter-ocular suppression during continuous flash suppression (CFS) and dichoptic visual masking using a transient onset target stimulus and a variety of stimulus / mask temporal manipulations. We show that target duration, timing of target onset, and mask frequency are key aspects of inter-ocular suppression during CFS with transient targets. The differences between our results and sustained target CFS studies suggest that two distinct mechanisms are involved in the detection of transient and prolonged target stimuli during CFS. Our results provide insight into the dynamics of CFS together with evidence for similarities between transient target CFS and dichoptic visual masking.